Responsabilidade social corporativa e certificação pela norma SA8000: um estudo de caso - Lima, Alcindo Martins (2008)
The transformations in the business world and in international geopolitical organization have brought severe consequences to the world of work. From the 80 s on, we have seen changes in the behavior of companies so that they could adapt themselves to the new model of the capital expansion, requiring new paradigms of management. The moviment towards social responsibilities of corporations fits into this process as a perspective of reaction and hope for a new cycle of development. This cycle is characterized by an ethics position, respect to environment and greater social justice In this thesis, we try to explain the evolution of the movement for Social Responsibility, understand its concepts and name its instruments. This study uses different sources of data, research in books, journal, internet and documents in companies. We also analyse, trought a case study, the way in wich the attention to the requisites for certification trought the norm SA8000 can contribute or limit the management of humam resources related to the requirements of the present levels of competion in an average company of the metal-mechanic sector of Rio Grande do Sul.